Implementasi Sistem Informasi Penerimaan Murid Baru (SPMB) Berbasis Web dengan Seleksi Otomatis Berdasarkan Nilai dan Lokasi Calon Siswa - Muhammad Yunus Rangkuti; Hendrawan Wibowo; Setyawan Dwi Prakoso; Ilham Nastiar (shofanah Media Berkah, 2026)
The student admission process in many schools is still conducted manually, including data recording, selection, and announcement of results. This conventional method often leads to inefficiency, data inaccuracies, and delays in decision-making. This study aims to design and develop a web-based Student Admission System (SPMB) to assist schools in managing the registration and selection of prospective students in a computerized manner. The system allows administrators to input applicant data, perform automatic selection based on predefined criteria such as academic average scores and distance from the student’s residence to the school, and display selection results efficiently. The implementation results indicate that the proposed system improves the efficiency, accuracy, and transparency of the student admission process. By automating data management and selection procedures, the web-based SPMB application provides an effective solution to support school administrative activities.